Team O2AS' approach for the task-board task of the World Robot Challenge 2018. (17th April 2020) - Nie, Kaidi; von Drigalski, Felix; Triyonoputro, Joshua C.; Nakashima, Chisato; Shibata, Yoshiya; Konishi, Yoshinori; Ijiri, Yoshihisa; Yoshioka, Taku; Domae, Yukiyasu; Ueshiba, Toshio; Takase, Ryuichi; Zhang, Xinyi; et al.
ABSTRACT: In this paper, we describe the approach of Team O2AS to complete the task-board task of the World Robot Challenge 2018, held in Tokyo. We use a custom gripper and graspable tools with in-built compliance to work with various kinds of parts, increase robustness against uncertainties, and to avoid complicated control strategies. The robots are able to finish all the sub-tasks without the need to exchange grippers. The main idea is to use mechanical compliance and self-centering mechanisms to deal with uncertainty. This is achieved by aligning the objects using either the gripper and tools, or by the design of the robot motions. GRAPHICAL ABSTRACT: